(untitled) - Siddayao, Corazón M. (Kuala Lumpur, 1978)
The purpose of this study is to try and answer the question: 'What are the potentials for conflicts or cooperation among nations arising from the search for petroleum resources in the seabeds of South-East Asia?' The problem of conflicts or cooperation among nations is a topic that has many facets and may involve a multitude of issues, for example, legal, economic, technical, security, social, etc.
Keywords: Petroleum industry and trade,Công nghiệp dầu khí và thương mại; Asia, southeastern,Đông Nam Á